2000
DOI: 10.1063/1.480610
|View full text |Cite
|
Sign up to set email alerts
|

Influences of concerted cluster diffusion on single-file diffusion of CF4 in AlPO4-5 and Xe in AlPO4-31

Abstract: Traditional models of single-file diffusion in zeolites assume that adsorbate diffusion mechanisms at high and dilute pore loadings are identical. Atomistic models of single file systems, in contrast, have shown that clusters of adsorbed molecules can diffuse via concerted motions that are not available to individual adsorbates. We report molecular dynamics simulations of CF 4 clusters in AlPO 4 -5 and Xe clusters in AlPO 4 -31. We have used these simulations to characterize the diffusion and dissociation mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…For example, Sholl and Fichthorn have shown using molecular dynamics (MD) simulations how concerted motions of clusters of water affects its overall transport in molecular sieves [238]. Similarly, Sholl and Lee also showed that concerted motions of clusters of CF 4 and Xe in AlPO 4 -5 and AlPO 4 -31 zeolites, respectively, contribute significantly to their overall mobilities [239]. Concerted motion has also been predicted to occur in transport across carbon nanotubes [240].…”
Section: Pore Transportmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, Sholl and Fichthorn have shown using molecular dynamics (MD) simulations how concerted motions of clusters of water affects its overall transport in molecular sieves [238]. Similarly, Sholl and Lee also showed that concerted motions of clusters of CF 4 and Xe in AlPO 4 -5 and AlPO 4 -31 zeolites, respectively, contribute significantly to their overall mobilities [239]. Concerted motion has also been predicted to occur in transport across carbon nanotubes [240].…”
Section: Pore Transportmentioning
confidence: 97%
“…For example, coarse-grained treatments of concerted motion were developed by Sholl and Lee [239]. Concerted motion has also been implemented within lattice models of exclusion processes in a more draconian manner.…”
Section: Pore Transportmentioning
confidence: 99%
“…ZIF-65 has heterogeneous pores with the size of 3.4/10.4 Å where steric hindrance and topology effects become dominant for Xe preventing its diffusion from the pores. Single file diffusion of Xe is also observed in zeolite AlPO4-31 by molecular dynamics study of Sholl et al [32]. Since we do not observe diffusion of Xe, Xe permeability and permeation selectivity values are not calculated for ZIF-65.…”
Section: Resultsmentioning
confidence: 51%
“…The essential difference between the normal diffusion and SFD lies in the dependence of mean-squared displacement of particles on the time interval t. In normal diffusion, MSD is proportional to t, while in SFD, MSD grows as √ t with respect to time. Such a dependence of MSD on √ t has been observed in many single-file systems in experiments [25][26][27][28] as well as in molecular simulations [29][30][31][32].…”
Section: Introductionmentioning
confidence: 85%